From the Eastern Tip of Sumatra: Bringing Local Wisdom to Life Through English-Language Films - Efrizah, Doni; Subambang H; Nasution, Nina Andriany; Febrio Ardly Saefsan; Vivi Oxana Putri (Unram Journal of Community Service, 2025)
This community service program was implemented in Secanggang Village, Langkat Regency, at the eastern tip of Sumatra, a region renowned for its rich Malay traditions. The initiative aimed to preserve and promote local wisdom by producing an English-language short film, while simultaneously enhancing the English proficiency and acting skills of the younger generation. Using a participatory, training-based approach, participants received practical instruction in English communication and performance, which they applied directly in film production. Supported by Arti Studio Creative Network, the program encompassed language training, acting workshops, and technical assistance in filmmaking. The 28-minute film highlighted key aspects of Malay culture, including the historical Datuk Secanggang House, the Tepak Sirih Dance, and traditional culinary practices, thereby blending cultural documentation with global communication. Evaluation results indicated notable improvements in participants’ speaking confidence, acting ability, and cultural awareness. Beyond functioning as a work of visual art, the film served as a medium for language education, cultural preservation, and community empowerment. This activity demonstrates that local traditions can be creatively sustained through the integration of international languages and film. Future efforts should focus on sustained film production, broader community engagement, and optimized digital dissemination to ensure Malay cultural heritage from North Sumatra reaches a global audience.